2008
DOI: 10.1007/s00125-008-1149-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1, but not glucose-dependent insulinotropic peptide, inhibits glucagon secretion via somatostatin (receptor subtype 2) in the perfused rat pancreas

Abstract: Aims/hypothesis The glucose-lowering effect of glucagonlike peptide-1 (GLP-1) is based not only upon its potent insulinotropic actions but also on its ability to restrain glucagon secretion. Surprisingly, the closely related glucose-dependent insulinotropic peptide (GIP) stimulates glucagon release. We examined whether the islet hormone somatostatin, which strongly inhibits glucagon secretion, is involved in this divergent behaviour. Methods At 1.5 mmol/l glucose and therefore minimal insulin secretion, the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 54 publications
12
163
2
4
Order By: Relevance
“…An indirect pathway involving GLP1R-dependent stimulation of somatostatin secretion seems likely because somatostatin receptors generally are coupled to inhibition of their target cells. This concept is supported by studies on perfused pancreas that showed a loss of GLP-1-inhibited glucagon release in the presence of somatostatin receptor inhibitors (76).…”
Section: Gut Endocrine Regulation Of Glucose Metabolismmentioning
confidence: 87%
“…An indirect pathway involving GLP1R-dependent stimulation of somatostatin secretion seems likely because somatostatin receptors generally are coupled to inhibition of their target cells. This concept is supported by studies on perfused pancreas that showed a loss of GLP-1-inhibited glucagon release in the presence of somatostatin receptor inhibitors (76).…”
Section: Gut Endocrine Regulation Of Glucose Metabolismmentioning
confidence: 87%
“…The mechanism whereby GLP-1 inhibits glucagon secretion has been suggested to be indirect relative to its effects on the beta cell (insulin, zinc, glutamate) (58). However, GLP-1 also suppressed glucagon secretion in subjects with type 1 diabetes and no residual beta cell function (59), and recent studies in isolated perfused rat pancreas demonstrated inhibition of glucagon secretion by GLP-1 at glucose levels too low to cause measurable insulin secretion (60) 3) Effects on appetite and food intake. GLP-1 inhibits appetite and food intake in normal subjects(64) as well as in obese subjects with T2DM(65;66), and it is thought that GLP-1 is one of the gastrointestinal hormones that normally regulate food intake(42).…”
Section: Effects On Glucagon Secretionmentioning
confidence: 99%
“…The latter seems to be under a tonic control by somatostatin. Incretins seem to act within the endocrine pancreas via SSTR2 (33). The early, glucose-induced release of insulin primarily depends on this entero-insular axis.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Depending on the dose, SSAs inhibit meal-dependent insulin secretion as well as GLP1 secretion. As a result, they also inhibit the protective effects of GLP1 and glucagon on adipogenesis and lipid metabolism (33). The therapeutic use of SSA such as octreotide and lanreotide, which mainly act via an inhibition of SSTR2 and 5, does not lead solely to an inhibition of somatotrophic pituitary cells, but they ubiquitously stimulate the receptors and convey complex metabolic effects which are currently only clarified in part.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%